Pretrial negotiations under optimism. (4th April 2019) - Vasserman, Shoshana; Yildiz, Muhamet
Abstract: We develop a tractable and versatile model of pretrial negotiation in which the negotiating parties are optimistic about the judge's decision and anticipate the possible arrival of public information about the case prior to the trial date. The parties will settle immediately upon the arrival of information. However, they may also agree to settle prior to an arrival. We derive the settlement dynamics prior to an arrival: negotiations result in either immediate agreement, a weak deadline effect—settling at a particular date before the deadline, a strong deadline effect—settling at the deadline, or impasse, depending on the level of optimism. Our findings match stylized facts.